2013
DOI: 10.1007/s11999-013-3100-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Rewording MRI Reports Improve Patient Understanding and Emotional Response to a Clinical Report?

Abstract: Emotional response, satisfaction, usefulness, and understanding were all superior in MRI reports reworded for lower reading level and optimal emotional content and optimism. Given that patients increasingly have access to their medical records and diagnostic reports, attention to health literacy and psychologic aspects of the report may help optimize health and patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Although patients desire access to their report [37], and are increasingly receiving it through their electronic medical records, only two guidelines consider the patient, and only to state that the reporting radiologist should consider that the patient may read the report. Methods to reduce patient distress and anxiety that have been explored include rewording imaging reports to use simpler and more neutral language [38], including patient-oriented explanations of complex medical terms along with diagrams [39,40], and lay language summaries [41]. Insertion of benchmark epidemiological data providing information similar to normal ranges for laboratory tests has also been proposed and investigated [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Although patients desire access to their report [37], and are increasingly receiving it through their electronic medical records, only two guidelines consider the patient, and only to state that the reporting radiologist should consider that the patient may read the report. Methods to reduce patient distress and anxiety that have been explored include rewording imaging reports to use simpler and more neutral language [38], including patient-oriented explanations of complex medical terms along with diagrams [39,40], and lay language summaries [41]. Insertion of benchmark epidemiological data providing information similar to normal ranges for laboratory tests has also been proposed and investigated [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…While imaging results and their interpretation was the least mentioned theme in the general themes categories of phase 1, it was the second most common theme in the explicit fear-related themes in phase 4. Patients' worries, complaints and concerns regarding radiological reports have been previously described (Bossen, Hageman, King, & Ring, 2013;Hong et al, 2017;Stewart & Loftus, 2018). Medical jargon, specifically if contained in imaging results, is often threatening to patients, and may be misinterpreted and negatively affect their emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Medical jargon, specifically if contained in imaging results, is often threatening to patients, and may be misinterpreted and negatively affect their emotions. For that reason, it has been proposed to reword reports and correspondence in a less threatening and more optimistic way in order to ensure better understanding of the report and its meaning (Bossen et al., 2013). Furthermore, it was suggested that the use of alternative terms with patients may help to prevent negative emotions and lead to the adoption of better coping strategies (Stewart & Loftus, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The mock laboratory test report used in the patient survey was based on a typical US commercial laboratory report that physicians and patients receive. However, this typical report was revised based on the findings from the physician study within this research and based on recommendations for patient-facing health care information, as discussed in patient engagement literature 14,24. The resulting mock laboratory report included explanatory information about the laboratory test and patient resources based on information from quality patient educational websites written by health care professionals 27,32.…”
Section: Methodsmentioning
confidence: 99%